2013
DOI: 10.1590/s0100-736x2013001000001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging animal viruses: real threats or simple bystanders?

Abstract: The list of animal viruses has been frequently added of new members raising permanent concerns to virologists and veterinarians. The pathogenic potential and association with disease have been clearly demonstrated for some, but not for all of these emerging viruses. This review describes recent discoveries of animal viruses and their potential relevance for veterinary practice. Dogs were considered refractory to influenza viruses until 2004, when an influenza A virus subtype H3N8 was transmitted from horses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…in herds (FÁVERO et al, 2017). While prevalence rates ranging from 22.2% to 85.4% (FLORES et al, 2013;QUINCOZES et al, 2007;ALMEIDA et al, 2013) have been reported for BVDV, seropositivity rates between 18% and 90% were found for BoHV-1 in non-vaccinated herds in different geographic regions of Brazil (LOVATO et al, 1995;TAKIUCHI et al, 2001;DIAS et al, 2013). The Leptospira spp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…in herds (FÁVERO et al, 2017). While prevalence rates ranging from 22.2% to 85.4% (FLORES et al, 2013;QUINCOZES et al, 2007;ALMEIDA et al, 2013) have been reported for BVDV, seropositivity rates between 18% and 90% were found for BoHV-1 in non-vaccinated herds in different geographic regions of Brazil (LOVATO et al, 1995;TAKIUCHI et al, 2001;DIAS et al, 2013). The Leptospira spp.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we have also reported the occurrence of antibodies against BoHV-1, BVDV and Leptospira spp. In Brazil, previous seroepidemiological studies have indicated a significant dissemination of BVDV, BoHV-1 (AFFONSO et al, FINO et al, 2012;FLORES et al, 2013), and Leptospira sp. in herds (FÁVERO et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil, prevalence rates of BVDV range from 22.2% to 85.4% [ 18 , 37 , 38 ], and seropositivity frequencies of BoHV-1 between 18% and 90% were frequently observed in non-vaccinated herds throughout the different geographical areas of Brazil [ 39 – 41 ]. In the Northeastern Brazil, seroprevalences for BVDV infection of 72.6% [ 42 ] and 51.1% in family farms [ 43 ] in Pernambuco state, and for BoHV-1 infection of 79.5% [ 44 ] also in Pernambuco state, 62.67% [ 45 ] in Sertão of Paraíba and 63.23% [ 46 ] in Maranhão state have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of BVDV and BoHV-1 have numerous references available all over the world, with variable values, but generally higher, depending on the control measures practiced [ 15 ]. In Brazil, regional data obtained from serological surveys reveal significant spread of the virus in beef and dairy herds [ 16 – 18 ]. In the state of Paraíba, Thompson et al [ 19 ] found anti-BVDV antibodies in 22.2% of animals and 88.9% of herds and anti-BoHV-1 antibodies in 46.6% of animals and 100% of herds.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of an One Health approach, the characterisation of novel viruses, especially coronaviruses in animals might contribute to guide new policies for zoonotic disease control, in addition to protecting endangered animals. (11,12)…”
mentioning
confidence: 99%